2020
DOI: 10.3390/ani10030416
|View full text |Cite
|
Sign up to set email alerts
|

Protected Organic Acids Improved Growth Performance, Nutrient Digestibility, and Decreased Gas Emission in Broilers

Abstract: We investigated the effects of a blend of organic acids (OAs) and medium-chain fatty acids (MCFAs) supplementation in 800 1-d-old male Ross 308 broiler chickens (42 ± 0.90 g) in a 7-week study. Broiler chicks were randomly allocated into one of the five dietary treatments (16 birds per pen with 10 pens per treatment). Dietary treatments consisted of corn-soybean meal based basal diet and the basal diet supplemented with blend of OAs and MCFAs at 0.25, 0.5, 0.75 g, and 1 g per kg of feed. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…With regard to the effect of gender on the measures shown in the Tables (3 and 4), gender had no significant effect on the carcass characteristics. These insignificant results agreed with those of Nguyen and Kim (2020) who reported that increasing addition of the blend of organic acids and medium-chain fatty acids did not affect pH, the color of breast muscle, cooking loss, breast meat yield, and organ weight percent. Similarly, Dorra et al (2013) and Sherif (2018), reported that the supplementation of organic acids in growing diets had no significant effects on carcass traits of the rabbits.…”
Section: Carcass Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to the effect of gender on the measures shown in the Tables (3 and 4), gender had no significant effect on the carcass characteristics. These insignificant results agreed with those of Nguyen and Kim (2020) who reported that increasing addition of the blend of organic acids and medium-chain fatty acids did not affect pH, the color of breast muscle, cooking loss, breast meat yield, and organ weight percent. Similarly, Dorra et al (2013) and Sherif (2018), reported that the supplementation of organic acids in growing diets had no significant effects on carcass traits of the rabbits.…”
Section: Carcass Characteristicssupporting
confidence: 92%
“…The supplementation of organic acids on diets can lower gastric pH thereby accelerates the conversion of pepsinogen to pepsin and improve the absorption rate of proteins, amino acids, and minerals. This may contribute not only to improve performance, but also reducing nitrogen and phosphorus excretion with decreasing environmental pollution (Nguyen and Kim, 2020). Organic acids have many additional A effects beyond antibiotics effects, include decrease the pH of digestive tract, increase of pancreatic secretion, alimentary effects on the gastrointestinal mucosa (Dibner and Buttin, 2002), and improve the color and the firmness of meat subsequently increasing carcass quality Citric acids exert anti-microbial activity in rabbits and improve nutrients utilization and consequently rabbit performance (Uddin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[17, 20, 23, 25-30, 32-34, 65] and Salmonella spp. [42,46,51,54]. Our results showed great variability in the effectiveness of this group of control measures (Table 4), which is in line with several reviews carried out in the past, which conclude that the exact impact of these feed additives is still unknown [8,12,62,66].…”
Section: Campylobacter and Salmonellasupporting
confidence: 89%
“…[15-34, 35•, 36-38] and Salmonella spp. [15,19,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] were carried out in thirteen and eleven different countries, respectively. For both pathogens, most of the pre-harvest interventions were assessed in lab-based challenge trials (65% and 82%), while the remaining trials were field trials where no experimental infection was performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, Sweeney et al [ 40 ] stated that weaning pigs fed S. cerevisiae related β-glucans supplementation had significantly reduced E. coli counts without affecting Lactobacillus counts. Ammonium and hydrogen sulfide (harmful) are considered as the major hazardous gases of pig manure which lead to environmental pollution [ 41 ]. The elevated level of NH 3 and H 2 S not only cause a health risk to animals but also to the workers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%